Management and Surgical Treatment of Prolapsed Ectopic Ureterocele in a Pediatric Patient - Boumediene Abou-Bekr; Mohamed Djelad; Yamina Ouadah; Soumia Chikh Bled; Hayat Meftah (Medical Research and Its Applications Vol. 10, 2024)
Ureterocele is a urinary malformation that presents diagnostic and management challenges due to its rarity and unusual presentation. It is essential to raise awareness among pediatric urology practitioners and specialists of these complications and implications to ensure good management under appropriate load. We reported the case of a 12-month-old girl presenting with an ectopic ureterocele prolapsed into the vulva. Urinary catheterization was used as emergency treatment to minimize ureterocele. The patient then underwent a superior polar heminephrectomy at 17 months of age, which partially resolved the problem. A year later, she again sought treatment for her prolapse. This time, ureterecelectomy with ureteral reimplantation was performed, which resulted in complete recovery. Non-consensual management of this malformation must be initiated as early as possible to prevent complications. The first goal of treatment was to decompress the prolapsed ureterocele and remove it endoscopically.